Social Media Usage and Social Capital as Determinants of Oil Palm Integration Practices Among Smallholders in East Malaysia - Ab Rahman, Abdul Hafiz; Abdullah, Azlina; Johari, Mohammad Lui; Yusoff, Sarina; Rasli, Fateen Nabilla (Advances in Social Sciences Research Journal, 2024)
Social media plays an increasingly important role in expanding social networks, which may influence the development of social capital among rural communities. This study investigates the relationship between social capital, social media usage, and the adoption of integration practices among oil palm smallholders in East Malaysia. A survey of 194 smallholders revealed that those with higher education levels had significantly higher bonding social capital (p < 0.05). Additionally, smallholders who had used WhatsApp for five years or more exhibited significantly higher levels of both bonding and bridging social capital (p < 0.05). The study found a significant association between bridging social capital and integration practices, particularly non-agricultural activities, but no significant link with bonding social capital. Logistic regression showed that smallholders with higher bridging social capital were more likely to engage in non-agricultural integration practices (OR = 5.64, 95% CI = 2.30–13.83, p < 0.001). These findings suggest that targeted efforts to enhance social media literacy could strengthen social capital and diversify the economic activities of smallholders. Expanding future research to cover a broader geographical area with varying internet accessibility is recommended.